Application Of The Market Day Based Entrepreneurship Learning Model In Building Generation Entrepreneurs - Nanda Ayu Setiawati; Fadhilah Syam Nst; Rozina Zahara (CV. Pusdikra Mitra Jaya, 2022)
This entrepreneurial spirit is seen as a character trait that has personal strength in facing the challenges of the world. The purpose of the research is to make students as entrepreneurs who are expected to be able to become the driving force of the nation's progress. The entrepreneurial spirit possessed by students is a mental attitude and soul that is always active and creative, and strives to increase income from its business activities and help advance the nation's economy. There are 6 core values of entrepreneurship that can be integrated into early childhood learning, namely: independent, creative, risk-taking, leadership, action-oriented, and hard work. This study uses qualitative research. The research was conducted at SDN Keumuneng Hulu Kab. East Aceh, Nanggoroeh Aceh Darussalam Province. The research subjects were students in grades 1 to 6 of elementary schools, principals, teachers, parents/guardians of students, and the surrounding community. The data collection techniques used in this study were: interviews, observation, and documentation. This market day activity was carried out by dividing students into ten groups with 14-15 students in 1 group accompanied by 2 coordinating teachers. Each group gets different preparations or sales including, Fruits, vegetables, cheese, yogurt, milk, processed chicken, fish, cheese, processed pudding, tubers and juice. In addition, students must have an attractive and attractive sales stand.